COVID-19 vaccination motivation and underlying believing processes: A comparison study between individuals with affective disorder and healthy controls - Dalkner, Nina; Fleischmann, Eva; Fellendorf, Frederike T.; Wagner-Skacel, Jolana; Schönthaler, Elena M. D.; Bengesser, Susanne; Häussl, Alfred; Tietz, Sophie; Tmava-Berisha, Adelina; Lenger, Melanie; Reininghaus, Eva Z. (Frontiers in Psychology, 2022)
Background Believing processes represent fundamental brain functions between cognition and emotion. Shortly before the introduction of a compulsory vaccination against COVID-19 in Austria, motives and underlying believing processes regarding the vaccination were collected in individuals with affective disorder (AD) and healthy controls (HC). Methods 79 individuals with AD and 173 HC were surveyed online to assess believing processes with the parameters of the credition model (narratives, certainty, emotion, mightiness) about (1) the coronavirus itself and (2) why someone is vaccinated or not. In addition, we calculated congruence scores between content of narrative and type of emotion and divided the narrative content into positive, negative, and indifferent. Results There were no differences in vaccination status between AD and HC. Higher levels of certainty were observed in HC compared to AD in both vaccinated and unvaccinated individuals. The effects were higher when asked about the motivation to vaccinate or not than about the coronavirus itself. In HC, more positive emotions and more congruence between emotions and narratives were reported during believing in their vaccination motives. No group differences were found in mightiness for both items. Independently from diagnosis, unvaccinated people had high levels of certainty and more negative emotions and narratives while believing in their motives for not getting vaccinated. Conclusion When believing about the COVID-19 vaccination, individuals with AD were more uncertain and experienced fewer positive emotions than HC, although both groups did not differ in vaccination status. These effects were not that strong when believing about the coronavirus in general.